Community-based health insurance: a comprehensive review of literature and lessons for future development - Abubaker, Reem Abbas; Zakariyah, Habeebullah (Asian Scholars Network, 2023)
This paper comprehensively reviews the existing Community-Based Health Insurance (CBHI) and provides valuable insights and lessons for its future development. The development of community-based health insurance (CBHI) has a practical approach to enhancing healthcare service accessibility, particularly in socioeconomically disadvantaged regions. This literature review examines the main components, operational models, and challenges of CBHI implemented in some low-income countries. The findings highlight the potential for CBHI in improving financial protection, health care utilization, and health outcomes for communities. In addition, the review identifies critical success factors, including effective governance and community involvement. Furthermore, challenges to implementing the CBHI are articulated, providing valuable insights for policymakers, practitioners, and researchers. The document presents proposals for the future advancement of the Community-Based Health Insurance (CBHI) program. This comprehensive review is a constructive resource for stakeholders involved in designing and implementing CBHI programs, contributing to advancing healthcare systems.